A systematic review of possible interactions for herbal medicines and dietary supplements used concomitantly with disease‐modifying or symptom‐alleviating multiple sclerosis drugs. (24th February 2021) - Petersen, Malene J.; Bergien, Sofie O.; Staerk, Dan
Abstract : Multiple Sclerosis (MS) is a demyelinating disease affecting the central nervous system, with no curative medicine available. The use of herbal drugs and dietary supplements is increasing among people with MS (PwMS), raising a need for knowledge about potential interactions between conventional MS medicine and herbal drugs/dietary supplements. This systematic review provides information about the safety of simultaneous use of conventional MS‐drugs and herbal drugs frequently used by PwMS. The study included 14 selected disease‐modifying treatments and drugs frequently used for symptom‐alleviation. A total of 129 published papers found via PubMed and Web of Science were reviewed according to defined inclusion‐ and exclusion criteria. Findings suggested that daily recommended doses of Panax ginseng and Ginkgo biloba should not be exceeded, and herbal preparations differing from standardized products should be avoided, especially when combined with anticoagulants or substrates of certain cytochrome P450 isoforms. Further studies are required regarding ginseng's ability to increase aspirin bioavailability. Combinations between chronic cannabis use and selective serotonin reuptake inhibitors or non‐steroidal antiinflammatory drugs should be carefully monitored, whereas no significant evidence for drug‐interactions between conventional MS‐drugs and ginger, cranberry, vitamin D, fatty acids, turmeric, probiotics or glucosamine was found.